Managing Poststroke Fatigue Using Telehealth: A Case Report. - Boehm, Nicole; Muehlberg, Hannah; Stube, Jan E. (American Journal of Occupational Therapy)
OBJECTIVE. The objective of this study was to examine the effectiveness of delivering Managing Fatigue: A Six-Week Course for Energy Conservation via telehealth for a 70-yr-old man with poststroke fatigue (PSF). METHOD. For this pilot case study, a questionnaire developed by the authors and the Patient-Reported Outcomes Measurement Information System Fatigue Short Form 7a were used for screening. The study was implemented via teleconference over an 8-wk period. The Fatigue Impact Scale (FIS) and the Canadian Occupational Performance Measure (COPM) were used to gather pretest and posttest data. RESULTS. After the participant completed the course, decreased fatigue impact was noted on the FIS, and modestly improved occupational performance and satisfaction were evidenced by the COPM. CONCLUSION. For this single participant experiencing PSF, performance and satisfaction on the COPM guardedly improved and fatigue impact decreased after participation in the energy conservation course offered by teleconference, a form of telehealth delivery. Further research is recommended with larger sample sizes.